Pertanggung Jawaban Pidana UU ITE Terhadap Pembobolan Data Pribadi di Era Serba Digital - Faisal, Bagus Imam; Indriani, Dian Eka (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2022)
The advancement of information technology in Indonesia is especially very rapid once the cell, a computer, and the internet have proven to have a positive impact on better human life. Behind of ease offered by a computer and the internet, having turns a dark side that can destroy life and human culture itself. Methods used in this research is by using an approach to a problem juridical normative namely to the concept of law as the norm, rules, the principle, by adopting regulations that are described in a sort of descriptive set based on a problem with various the rules of law and literature, and search for an opinion the law of issues object the problem. Private data protection on an electronic system in law information and electronic transaction ( ITE) covers protection from the use without any permission, the protection of the creation of this electronic system, as well as efforts to protect leakage of access as well as illegal interference. Criminal sanctions that had been established in the act of ITE in the form of criminal sanctions prison and fines. So common interpretation surely has governed by data protection to the provisions in government regulation number 71 in 2019 on the implementation of the system and electronic transaction article 30-33 and article 35 which was about activities that are not allowed.